Management of muscle trigger points causing subacromial pain using dry needling technique — a case report (Journal of the Pakistan Medical Association, 2020)
Abstract We present a case of a 22-year-old university sportsman who presented at a private hospital in Lahore in December 2018 with complaint of severe pain in the anterolateral aspect of the right shoulder after playing cricket. On palpation, greater tubercle of the right shoulder was found to be tender along with the muscle belly of supraspinatus. A muscle trigger point was identified during palpation, while painful arc was also present on abduction. Physical tests, including Hawkins-Kennedy, Neers sign and empty can test, were found to be positive. The musculoskeletal ultrasound revealed that supraspinatus and bicep tendons were intact. The patient was managed by dry needling technique. The novelty of this clinical trial was the application of trigger point dry needling for the management of subacromial pain syndrome. Muscle trigger point symptoms can present as rotator cuff tears, supraspinatus tendonitis and bicipital tendonitis leading to misdiagnosis. Continuous...